Protecting African rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
West African rice producers are invoking their right to protect their commodities, as laid down in the latest draft agreement on agriculture drawn up by the World Trade Organization (WTO) to regulate imports to the continent. In December 2004, delegates f